Legal Accountability of Medical Personnel in Installation and Removal of Ventilators in Patient Life Support Efforts in the Covid-19 Pandemic - Sushanty, Vera Rimbawani (Jurnal Independent, 2023)
AbstractThis research was conducted to determine the legal basis for management in the decision-making process for installing and releasing ventilator use in critical patients during the COVID-19 pandemic. In addition, to find out the legal responsibility for installing and removing the use of ventilators in critical patients during the COVID-19 pandemic by medical personnel. The research method used is juridical normative or doctrinal legal research based on a statutory approach and a conceptual approach. This research uses legal material collection techniques based on document studies or library materials. Data collection in this research is done by analyzing it based on data, theory, and other references from the existing literature. The findings show that the legal basis of management in the decision-making process for installing and releasing the use of ventilators in critical patients during the COVID-19 pandemic refers to the provisions of Chapter 3 Articles 14 and 15 of Permenkes No. Chapter 4 Article 16 Permenkes No. 290 of 2008; and Chapter 5 Article 18 Permenkes RI Number 290 of 2008 concerning rejection of medical action, which can be done by a patient and or his / her closest family after receiving an explanation of the medical action to be performed. The legal responsibility for installing and removing ventilators for critical patients during the COVID-19 pandemic by medical personnel is based on the provisions of the Indonesian Medical Council, KODEKI, and the Medical Practice Law that medical actions are carried out without the patient's consent, so they may be subject to sanctions.Â